Chromosome-Scale Assembly and Characterization of the Albino Northern Snakehead, Channa argus var. (Teleostei: Channidae) Genome - Zhou, Chaowei; Li, Yan; Zhou, Yan; Zou, Yu; Yuan, Dengyue; Deng, Xingxing; Lei, Luo; Su, Jian; Zhu, Chengke; Ye, Hua; Luo, Hui; Lv, Guangjun; et al. (Frontiers in Marine Science, 2022)
Northern snakehead, Channa argus (C. argus), is an important economic and ecological fish species. The wild population of the species was sharply declined in the last decade. A high-quality reference genome could lay a solid foundation for the genetic and conservation studies for C. argus. In this work, we report a chromosomal genome assembly with PacBio and Hi-C technology using the albino northern snakehead, a color variety of C. argus. A 644.1-Mb genome with 24 chromosomes was obtained with a contig and scaffold N50 of 11.78 and 27.8 Mb, respectively. We inferred that C. argus diverged from A. testudineus around 85.6 million years ago. 514 expanded gene families and 214 positively selected genes were identified in the C. argus genome. The chromosome-level genome provides a valuable high-quality genomic resource for population, as well as genetic and evolutionary studies for C. argus and other species in Channidae.